Pengembangan LKPD Berbasis Project Based Learning (PjBL) Pada Muatan Ipas Untuk Meningkatkan Efektivitas Pembelajaran Peserta Didik Kelas IV MI Darussalam Kota Jambi - Zusniarni, Zusniarni; Nazurty, Nazurty; Sukendro, Sukendro (LPPM Institut Pendidikan Nusantara Global, 2024)
At this time, the implementation of the independent curriculum emphasizes students being able to be active in the learning process, student activity requires effectiveness that is conducive to achieving learning goals. This research aims to develop student worksheets (LKPD) based on project-based learning in science and technology learning on energy transformation material. The research validation subjects were linguists, material experts, and media experts. This research is development research using the R&D model with a 4-D development model consisting of Define, Design, Development, and Disseminate. Furthermore, the data collected is quantitative and qualitative data. Data collection used observation methods, structured interviews, document recording, and questionnaires. The data analysis used is qualitative descriptive and quantitative descriptive analysis techniques. Based on the data analysis, the results obtained, namely the results of a subject matter expert review, show that the project-based learning based LKPD is very good for use, especially in increasing the effectiveness of students in the learning process which is indicated by the results of individual tests showing that the project-based learning based LKPD is very good. Based on this, the project-based learning LKPD in science and science lessons on energy transformation is in very good qualifications and is suitable for use as teaching material for fourth-grade elementary school students.